A novel and robust method to quantify fatigue damage in fibre composite materials using thermal imagine analysis. (September 2021) - Eder, Martin A.; Sarhadi, Ali; Chen, Xiao
Highlights: Theoretical basis for using thermography to recover fatigue damage states in composite materials. Thorough experimental validation of the theoretical prediction. A simple and robust method to assess the high cycle fatigue damage stage from thermal videos. Abstract: This work proposes a novel and robust thermal imaging-based method suitable to quantify damage evolution stages in fibre-reinforced composite materials under fatigue loading. The method uses adiabatic hysteretic heating of the material to calculate the change of enthalpy by thermal imaging when the material undergoes fatigue damage. This work analytically corroborates the validity of using the calculated change of enthalpy to identify the three different fundamental fatigue damage stages of the material. The method is applied to two different types of notched sandwich specimens subject to constant amplitude fatigue loading. It is practically demonstrated that the characteristic curve progressions of the mechanically measured hysteretic dissipation curves are in good agreement with those of the enthalpy change computed by the proposed method.